Effect of fuel isotope mass on q-profile formation in JET hybrid plasmas. (10th July 2020) - Challis, C.D.; Brezinsek, S.; Coffey, I.H.; Fontana, M.; Hawkes, N.C.; Keeling, D.L.; King, D.B.; Pucella, G.; Viezzer, E.
Abstract: The initial current ramp phase of JET hybrid plasmas is used to optimise the target q-profile for main heating to allow access to high β and avoid MHD instabilities. Mixed protium-deuterium experiments, carried out at JET since the installation of the beryllium-tungsten wall, have shown that the q-profile evolution during this Ohmic phase varies systematically with average main ion isotope mass, indicating the need for re-optimisation for future T and mixed D-T experiments. Current diffusion modelling shows that the key factor was a reduction in electron temperature profile peaking as the hydrogenic isotope mass was increased. This was correlated with an increase in plasma radiation by metallic impurities, consistent with the increased sputtering yield by higher mass isotopes during the current ramp phase. Reduced electron temperature peaking can lead to magnetic shear reversal and the appearance of a 2/1 mode, which can lock, causing the JET massive gas injection system to be triggered to avoid an unmitigated disruption. The potential for a further reduction in electron temperature peaking in T and D-T plasmas could, therefore, result in an increased risk of disruptions. To mitigate this risk, electron temperature peaking measurements have been included in the real-time control system to allow this type of disruption to be avoided by central heating, density increase or early pulse termination. These experiments indicate the need for integrated modelling of impurity behaviour, including the plasma core, scrape-off layer and plasma wall interactions, to predict q-profile evolution in the current ramp phase and anticipate the effects of isotope changes.